Performance Management Systems in Healthcare Organizations: A Systematic Review of Impact on Staff Motivation and Patient Care - Ainun Ainun; Karlina Karlina; Ferawati Ferawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Performance management systems (PMS) play a critical role in healthcare organizations by influencing staff motivation and patient care quality. This systematic review examines recent literature from 2023-2024 to assess the impact of performance management systems on healthcare staff motivation and patient outcomes. A comprehensive search of academic databases identified 42 relevant studies focusing on various performance management frameworks including Balanced Scorecard, continuous feedback systems, and goal-setting approaches. The findings reveal that effective performance management systems positively influence staff motivation through three key mechanisms: satisfaction of psychological needs (autonomy, competence, and relatedness), provision of timely feedback, and alignment of individual and organizational goals. Evidence demonstrates that well-designed PMS incorporating Self-Determination Theory principles enhance autonomous motivation, work engagement, and job satisfaction while reducing burnout and turnover. Furthermore, performance management systems that emphasize continuous feedback, development-focused approaches, and recognition programs show significant positive associations with patient care quality, safety outcomes, and organizational performance. However, the review also identifies challenges including over-reliance on metrics, resistance to change, and potential for dysfunctional behaviors when systems are perceived as controlling rather than enabling. The study concludes that healthcare organizations should adopt enabling approaches to performance management that balance accountability with professional autonomy, integrate formative feedback mechanisms, and align performance measures with organizational values and strategic objectives. Future research should focus on longitudinal studies examining causal relationships and implementation strategies for sustaining effective performance management systems.